Edlink as Paperless Service: Strategic to Minimizing Paper Consumption in College Based on Eco-theology Perspective - Ilyas Adhi Purba; Muhammad Irsyad Elfin Mujtaba (Jurnal At-Tamwil: Kajian Ekonomi Syariah, 2026)
Purpose/Objective – This research aims to examine the use of Edlink as a paperless digital service in an effort to minimize paper consumption on campus, from an eco-theological perspective. Method – This research employs descriptive qualitative methods, collecting data through observation and a literature study. Findings – Edlink saves paper consumption, one of which is through implementing UTS and UAS alone, the campus saves expenses of around 2036 sheets of paper, or 4 reams, or saves costs of around Rp. 160,000 - Rp. 240,000. However, the campus must pay Rp. 11 million for using Edlink by Sevima. Edlink can save thousands of sheets of paper, but it still requires costs for using the application. Using Edlink from an eco-theology perspective in paperless form is a form of preserving green trees on Earth. In this context, efforts to reduce paper use not only have an impact on administrative efficiency but are also part of a commitment to preserving the environment, especially the sustainability of trees as the main source of raw material for paper. Limitations – This research only focuses on the use of Edlink as a paperless service in the IAI Badrus Sholeh Kediri campus environment, so the research results cannot be widely generalized to all universities that have different characteristics, policies, and levels of digital literacy. Originality/Value – The originality of this research lies in the integration of educational digital technology (Edlink) with an ecotheological perspective as an ethical and theological basis in an effort to minimize paper consumption on campus.